Photosynthetic performance of two maize genotypes as affected by chilling stress - K. Kosová; D. Haisel; I. Tichá (Plant, Soil and Environment, 2005)
The effect of chilling on light dependence of photosynthetic and chlorophyll a fluorescence characteristics in two maize genotypes CE 704 and CE 810 grown in a glasshouse during spring and autumn was studied. In spring, the net photosynthetic rate (PN) of CE 704 plants was not affected by chilling under moderate irradiance but it was strongly affected under a saturating one. This indicates that efficiency of photosynthetic apparatus was not affected by chilling but its capacity was decreased. Contrary to CE 704, CE 810 plants were not affected by chilling under saturating irradiance. In autumn, CE 704 plants adapted to chilling and no statistically significant differencies in PN and Fv/Fm between chilled and control plants in the whole range of irradiance were found. Enhanced activity of non-photochemical quenching (NPQ) in chilled CE 704 plants under saturating irradiance corresponded with an increased level of xanthophyll cycle pigments and an increased deepoxidation state of these pigments.